Working Time and Cigarette Smoking: Evidence from Australia and Great Britain - Angrave, David; Wooden, M; Charlwood, Andy (My University, 2014)
Cigarette smoking is a risk factor in a range of serious diseases, including cardiovascular disease, cancer, stroke and type II diabetes. Theory suggests that working long hours will increase smoking propensities among workers. Consequently there is a significant body of evidence on the relationship between working time and smoking. Results, however, are inconsistent and therefore inconclusive. This paper provides new evidence on how working time affects smoking behaviour using nationally representative panel data from Australia (from 2002 to 2011) and the United Kingdom (from 1992 to 2011). We exploit the panel design of the surveys to look at within-person changes in smoking behaviour over time as working time changes. In contrast to most previous studies, this means we control for time invariant aspects of personality and genetic inheritance that may affect both smoking propensities and choice of working hours. We find that working long hours tends to increase the chances that former smokers will relapse, reduce the chances that smokers will quit and increase cigarette consumption among regular smokers, and that these effects tend to become more pronounced for workers who usually work very long hours (50 or more hours a week) compared to those who work moderately long hours (40–49 h a week).
Keywords: Employment -- Hours; Health -- Addictive behaviours; Health and wellbeing; Labour market; Employment; Health; Addictive behaviours; Hours; Employment and unemployment; Health and wellbeing